Strafverfolgung von Tierschutzkriminalität - Bäcker, Eva Maria (Duncker & Humblot, 2025)
The investigation deals with the lack of enforcement of criminal law in the area of agricultural livestock farming. On the one hand, it focuses on the criminal liability risks for public prosecutors in connection with underenforcement of law. On the other hand, it provides an overview of the prosecution practice typically observed in the area of animal welfare criminal law as well as a solution approach based on empirical results to make the criminal prosecution of animal welfare offences more effective.